Das Herkunftslandprinzip der E-Commerce-Richtlinie und seine Auswirkung auf die aktuelle Mediengesetzgebung in Deutschland - Liesching, Marc (Schriftenreihe Medientheorie & Medienrecht, 2020)
Are Germany's current efforts to implement strict national legal requirements for social networks based in other EU member states compatible with the country of origin principle? Are there exceptions to which the federal and state legislators can rely on media, network and youth protection law? Or do the German regulations and proposed regulations violate European law? The first volume of the new series on Media Law & Media Theory examines the issues, taking into account the case law of the ECJ and the communications of the EU Commission.